Secure image transmission over wireless network - A. Aliesawi, Salah; S. Alani, Dena; M. Awad, Abdullah (International Journal of Engineering and Technology, 2018)
The advances recently seen in data compression, and communication systems, have made it viable to design wireless image transmission systems. For many applications such as confidential transmission, military and medical applications, data encryption techniques should be also used to protect the confidential data from intruders. For these applications, both encryption and compression need to be performed to transmit a message in a fast and secure way. Further, the wireless channels have fluctuating channel qualities and high bit error rates. In this paper, a new scheme based on encryption and channel coding has been proposed for secure image transmission over wireless channels. In the proposed scheme, the encryption process is based on keys generator and Chaotic Henon map. Turbo codes are utilized as channel coding to deal effectively with the channel errors, multipath signal propagation and delay spread. Simulation results show that the proposed system achieves a high level of robustness against wide different of attacks and channel impairments. Further, it improves image quality with acceptable data rates.Â
Keywords: Chaotic Henon Map; Turbo Code; Image Transmission; Image Compression.